Space Closure Rate in Mandibular Canine Retraction by Ni-Ti Closed Coil Spring: A Clinical Trial (Medicine Today, 2021)
Introduction: In Majority of patients seeking orthodontic treatment, teeth must be extracted in order to obtain proper esthetics, occlusion, and stability as well as extraction of teeth is often a need to close residual space, after the initial decrowding and aligning. Pre adjusted fixed orthodontic appliances commonly utilize sliding mechanics for space closure with different types of force delivery systems. A variety of materials have been used as force delivery systems to close spaces between teeth as in the case of canine retraction after the extraction of premolars. Among all sliding or frictionless methods of canine retraction, super-elastic nickel titanium coil spring has a particular property in producing light continuous force at a long range of action, compared with previously available materials. Nickel-titanium closed coil spring, with a continuous action, might have some advantages in fixed appliance space closure mechanics.Materials and Methods: Over the period of one year from May 2015 to April 2016, this clinical trial was carried out and A total number of 20 patients (40 quadrants), who required canine retraction into first premolar extraction sites as part of their orthodontic treatment in the Department of Orthodontics of BSMMU selected as study population. The quadrants were affixed by nickel titanium closed coil springs (medium force, Ni-Ti extension spring, Ormco) with 200gm force measured by Correx Tension Gauge. Space closure was measured by means of direct measurement from the mesial surface of mesial wing of the 2nd premolar bracket and the distal surface of distal wing of the canine bracket with digital Vernier Calipers.Results: Mean space closer rate in mandibular canine retraction was 1.07 ± 0.12 mm/month by nickel-titanium (Ni-Ti) closed coil spring method with p value